2016
DOI: 10.1039/c5pp00197h
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical properties of symmetrically substituted diarylacetylenes and diarylbuta-1,3-diynes

Abstract: A series of symmetrically substituted diarylacetylenes and diaryl-1,3-butadiynes were prepared and studied with an emphasis on their spectral and photophysical properties. The photophysical characteristics of these compounds were studied in relation to their structures and the influence of solvent or temperature. The observed spectral and photophysical properties are explained using potential energy maps of the ground and excited states obtained from density functional theory calculations. The structure-proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Recently, Xie et al reported aggregation induced WLE from a carbazolyl- and phenothiazinyl-substituted benzophenone . There has been increasing interest in various applications and photophysics of butadiynyl derivatives in recent years. In a program aimed at the understanding of photophysics of some small butadiynyl fluorophores, we observed recently that a donor (−NMe 2 )–acceptor (−CN) substituted diphenylbutadiynyl derivative ( Me 2 NPBPCN ; Figure ) shows the WLE in acetonitrile (CH 3 CN) through a control of locally excited (LE) and exciplex emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Xie et al reported aggregation induced WLE from a carbazolyl- and phenothiazinyl-substituted benzophenone . There has been increasing interest in various applications and photophysics of butadiynyl derivatives in recent years. In a program aimed at the understanding of photophysics of some small butadiynyl fluorophores, we observed recently that a donor (−NMe 2 )–acceptor (−CN) substituted diphenylbutadiynyl derivative ( Me 2 NPBPCN ; Figure ) shows the WLE in acetonitrile (CH 3 CN) through a control of locally excited (LE) and exciplex emissions.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that perylene compounds substituted at the third position exhibit a bathochromic shift compared to perylenes substituted at the second position. Although aryl residues in diarylacetylenes are coplanar in their ground state, the rotation barrier is very low, and a number of conformations is present in solutions [56][57][58][59][60]. Compounds 3a-c exhibited fluorescence maxima in the 472-476 nm range, while compounds 3d-f showed fluorescence in the 440-442 nm range.…”
Section: Spectral Properties and 1 O2 Generationmentioning
confidence: 99%
“…It is important to note that the πσ* state in DPA is accessed with a vibronic coupling via low-frequency modes, which results in a dramatic increase of φ PL upon lowering the temperature from 0.002 (300 K) to 0.69 (77 K) . Similarly, DPB with two triple bonds shows temperature-activated nonradiative losses but was predicted to have less weakening in the CC bond than DPA. , In contrast, a large excess energy was estimated to achieve a σπ*/ππ* state intersection in DNB, which suggests that larger naphthyl end-groups reduce the possibility toward CC bending and thus eliminate transitions to the πσ* state.…”
mentioning
confidence: 99%
“…51 Similarly, DPB with two triple bonds shows temperature-activated nonradiative losses but was predicted to have less weakening in the CC bond than DPA. 52,53 In contrast, a large excess energy was estimated to achieve a σπ*/ ππ* state intersection in DNB, 54 which suggests that larger naphthyl end-groups reduce the possibility toward CC bending and thus eliminate transitions to the πσ* state.…”
mentioning
confidence: 99%